ALKYLATION OF BENZENE WITH LONG CHAIN OLEFINS OVER SOLID-ACID CATALYST (Journal of Engineering, 2009)
This investigation is concerned with the linear alkylbenzene production reaction by the alkylation of benzene with long chain olefins C10-C13 over various prepared solid acid catalysts. The alkylation process was studied at different reaction temperature, Weight hourly space velocities and with constant pressure and benzene/olefin ratio. The liquid-phase of alkylation of benzene with olefins carried out over preparedtungstophosphoric acid supported on SiO2 with 5, 10, 20 and 30 wt. % loading catalysts in a fixed bed reactor. Prepared tungstophosphoric acid supported over silica catalyst with 30 % loading gave the highest conversion of olefin to linear alkylbenzene (94% conversion) at 398K and 5h-1. The study of the kinetics of benzene alkylation with olefins over these prepared catalysts reveals that the reaction is second order. The value of Thiele modulus for each prepared catalysts is lower than 0.4 which means that diffusion free regime and the surface reaction is the limiting step for the alkylation process.